Patient centered outcomes in stroke: utility-weighted modified Rankin Scale results in a community-based study - Delfino, Carlos; Cavada, Gabriel; Hoffmeister, Lorena; Lavados, Pablo; Muñoz Venturelli, Paula (Frontiers in Neurology, 2025)
Background and aimsThe transformation of modified Rankin Scale (mRS) scores based on the corresponding utilities of health-related quality of life questionnaires can facilitate the capture of Patient-Centered Outcomes (PCO) in stroke. We aimed to derive utility-weighted modified Rankin Scale (UW-mRS) values by mapping mRS functional status to EQ-5D-3L scores in a population-based cohort of stroke patients.MethodsThe UW-mRS was obtained by analyzing the EQ5-D-3 L and mRS scores at 180 days after any stroke in the ÑANDU study, a large prospective community-based study in Chile. The mRS prediction was estimated using a linear regression adjusted by the EQ-5D-3L value. Generalized linear and binary logistic regression models were constructed to determine influencing factors of the UW-mRS, using STATA software (version 18.0).ResultsWe included 773 patients presenting with any stroke during 2015–2016: 48% were female, with a mean age of 71 years (SD 13.8), and 85% had an acute ischemic stroke (AIS). 82% of patients had a low socioeconomic status, 50% had less than 12 years of formal education, and only 32% lived in urban areas. UW-mRS values for mRS categories 0–6 at 180 days were 0.913, 0.694, 0.425, 0.249, −0.102, −0.347 and 0, respectively. Multivariable analysis identified age > 70 years (Coefficient β [β] -0.038 [Standard error SE 0.018], p = 0.032), prior mRS score 3–5 (β −0.556 [SE 0.197], p < 0.001), ischemic stroke (β −0.066 [SE 0.025], p = 0.010), and National Institutes of Health Stroke Scale (NIHSS) at admission>5 (β −0.015 [SE 0.002], p < 0.001) as significant predictors of worse UW-mRS scores (R2 = 70%) in the overall group. Sex-disaggregated analysis showed that age > 70 years was a significant predictor in males (β −0.069 [SE 0.024], p = 0.006), while presenting an AIS had a greater impact on female’s worse UW-mRS score (β −0.087 [SE 0.033], p = 0.010).ConclusionThese results present UW-mRS values derived from a population-based stroke study. Key determinants of health-related quality of life in post-stroke patients included age, prior disability, and stroke severity. Sex-disaggregated analysis revealed age being significant for males and AIS for females. Incorporating PCO as UW-mRS in stroke research can provide a more nuanced understanding of the impact of stroke on survivors, offering valuable insights for clinical decision-making and rehabilitation strategies across diverse healthcare contexts.